Comment on "Universal Out-of-Equilibrium Transport in Kondo-Correlated Quantum Dots: Renormalized Dual Fermions on the Keldysh Contour" - Aligia, Armando Angel (Amer Physical Soc, 2013)
Fil: Aligia, Armando Angel. Comision Nacional de Energia Atomica. Gerencia del Área de Energía Nuclear. Instituto Balseiro; Argentina;